ANALISIS JABATAN PEGAWAI DI BAGIAN HUKUM SEKRETARIAT DAERAH KABUPATEN SEMARANG - Septiyanti, Murni; Nurcahyanto, Herbasuki; Widowati, Nina (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2013)
In the arrangement of human resources management of civilian workers, basic information about the position information is needed that obtained from job analysis,therefore, the first step that must be done in the recruitment of employees is job analysis. The step that aimed is to obtain information about the characteristics ofexisting jobs in each work unit which further defined or formulated into each position. Job analysis activities is one of the crucial activities in Human Resource Management, particularly in the recruitment stage to determine the appropriate Human Resources at the required position, but the job analysis has not been carried out in the Law Section of Semarang District Secretariat which eventually led to thetransfer of employees to the Department of only the most qualified legal notice that is hindering the performance of the organization. Thus, it is necessary to formulate ananalytical description and specification of office in Semarang District Legal Department.